2022
DOI: 10.3389/fmicb.2022.1027317
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting phytomicrobiome of the neurotoxic actinorhizal species, Coriaria myrtifolia, and dispersal boundary of Frankia cluster 2 in soil outward compatible host rhizosphere

Abstract: The actinorhizal plant, Coriaria myrtifolia, is a neurotoxic plant species endemic to the western Mediterranean area, which forms a nitrogen-fixing symbiosis with members of Frankia cluster 2. Contrarily to other Frankia clusters, the occurrence and mode of dispersal for infective cluster 2 units outside of the host plant rhizosphere remains controversial. The present study was designed to investigate the structure of the microbiomes of C. myrtifolia phytosphere, rhizosphere, and soil samples extending outward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…At present, the presence of multiple Frankia strains in actinorhizal plants nodules has been demonstrated. Studies have shown that there were different Frankia strains in the nodules of Alnus , Myricaceae , and Coriaria , and their abundance was also different ( Clawson and Benson, 1999 ; Swanson et al., 2022 ; Vemulapally et al., 2022 ). For example, we found that Frankia from clusters I, II, and IV were simultaneously found in Myrica pensylvanica nodules, suggesting that different Frankia clusters could exist in the same host.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the presence of multiple Frankia strains in actinorhizal plants nodules has been demonstrated. Studies have shown that there were different Frankia strains in the nodules of Alnus , Myricaceae , and Coriaria , and their abundance was also different ( Clawson and Benson, 1999 ; Swanson et al., 2022 ; Vemulapally et al., 2022 ). For example, we found that Frankia from clusters I, II, and IV were simultaneously found in Myrica pensylvanica nodules, suggesting that different Frankia clusters could exist in the same host.…”
Section: Discussionmentioning
confidence: 99%